Unfolding the role of stress response signaling in endocrine resistant breast cancers - Clarke, Robert; Cook, Katherine L. (Frontiers in Oncology, 2015)
The unfolded protein response (UPR) is an ancient stress response that enables a cell to manage the energetic stress that accompanies protein folding. There has been a significant recent increase in our understanding of the UPR, how it integrates physiological processes within cells, and how this integration can affect cancer cells and cell fate decisions. Recent publications have highlighted the role of UPR signaling components on mediating various cell survival pathways, cellular metabolism and bioenergenics, and autophagy. We address the role of UPR on mediating endocrine therapy resistance and estrogen receptor-positive breast cancer cell survival.